2016
DOI: 10.1186/s41043-016-0051-3
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-pocket expenditure on prenatal and natal care post Janani Suraksha Yojana: a case from Rajasthan, India

Abstract: BackgroundThough Janani Suraksha Yojana (JSY) under National Rural Health Mission (NRHM) is successful in increasing antenatal and natal care services, little is known on the cost coverage of out-of-pocket expenditure (OOPE) on maternal care services post-NRHM period.MethodsUsing data from a community-based study of 424 recently delivered women in Rajasthan, this paper examined the variation in OOPE in accessing maternal health services and the extent to which JSY incentives covered the burden of cost incurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 47 publications
(34 reference statements)
2
41
2
1
Order By: Relevance
“…The average cost of the package of four antenatal care visits during pregnancy was $44 across the five public facilities and $160 in the private facility. A similar finding was documented in India, where the cost of antenatal care provision in private health facilities was more than double the cost of public sector provision [ 26 ]. In our study, the higher cost of ANC in the private clinic can be partly explained by the highly qualified and better-remunerated staff compared to public health facilities surveyed in this study.…”
Section: Discussionsupporting
confidence: 79%
“…The average cost of the package of four antenatal care visits during pregnancy was $44 across the five public facilities and $160 in the private facility. A similar finding was documented in India, where the cost of antenatal care provision in private health facilities was more than double the cost of public sector provision [ 26 ]. In our study, the higher cost of ANC in the private clinic can be partly explained by the highly qualified and better-remunerated staff compared to public health facilities surveyed in this study.…”
Section: Discussionsupporting
confidence: 79%
“…CHCs, due to a lighter load of childbirths, are better able to keep the perinatal care wards prepared for women. While other Indian studies describe a shortage of infrastructure, material and supply to support increased numbers of institutional childbirths [39,40,56], our review did not reveal other quantitative studies to prove or disprove our interpretations.…”
Section: Discussioncontrasting
confidence: 69%
“…The multi-front promotion of institutional childbirths by the Government of India has resulted in an exponentially increasing number of women coming to hospitals with the chief expectation of ensuring the safety of themselves and their neonates [3538]. However, the expansion in the number of labour rooms and necessary resources and infrastructure, especially in public health facilities, has not been proportional to rising demand [36,39,40]. Labour rooms have become crowded and understaffed and face shortages of equipment and material [17,40] and the documentation processes around childbirth have been described to be ‘too much to do concurrently with actual care provision’, with care providers relying on verbal communication rather than maintaining written documentation of decision-making around childbirth [17,41].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study in a rural setting in Nigeria, West Africa, showed that women and their families spent between US$9 and US$99 for use of maternal health services [ 37 ]. In India too, a recent study reported that households incurred a mean OOP expenditure of US$ 26 in public health facilities for the utilisation of maternal health services [ 38 ]. These studies bear resemblance to our study, given that the mean OOP costs were for use of maternal health services in public health facilities in the midst of fee exemptions or health insurance.…”
Section: Discussionmentioning
confidence: 99%